The Influence of Role Stress, Professionalism, and Independence on The Performance of Internal Auditors (A Case Study at the Inspectorate of North Sumatra Province) - Cindyana Oktari Siregar; Rini Indahwati; ⁠Ilham H. Napitupulu (Transpublika Publisher, 2025)
Internal auditors constitute an indispensable pillar in safeguarding accountability and institutional governance; nevertheless, their efficacy may be markedly contingent upon determinants such as role stress, professionalism, and independence. The present inquiry endeavors to ascertain and scrutinize the extent to which Role Stress impinges upon internal auditors’ performance, how Professionalism modulates their effectiveness, and the degree to which Independence fortifies their contributions within the Inspectorate of North Sumatra Province. Employing a quantitative methodological design, the investigation engaged a cohort of 75 internal auditors, with data procured through structured questionnaires and subsequently subjected to analytical treatment via SmartPLS. The empirical outcomes elucidate that Role Stress exerts a discernible impact on internal auditor performance, evidenced by a coefficient of 0.293, a t-statistic of 2.284, and a significance threshold of 0.05 (p < 0.05), with an f-square value of 0.234. Professionalism likewise manifests an influence, with a coefficient of 0.147, a t-statistic of 1.965, and significance at the 0.05 level (p < 0.05), albeit with only a minor explanatory magnitude as indicated by its f-square value of 0.072. Independence, conversely, emerges as the most potent determinant, with a path coefficient of 0.560, the preeminent t-statistic of 4.037, significance at 0.05 (p < 0.05), and a robust f-square index of 0.516.